Self-perceived preparedness of dental school graduates and the impact of COVID-19 pandemic on their confidence - Islam Abd Alraheam; Mays A AlAshqar; Susan Hattar; Abeer AlHadidi; Alaa Alhaddad; F A Sawair; Awni Alkayed (Wolters Kluwer Medknow Publications, 2021)
Introduction: Dental education quality is reflected by assessing graduating students' professional preparedness. Coronavirus disease 2019 (COVID-19) has had many challenges for dentistry some of which may have further long-term impacts on clinical practice, dental education, and dental research. Impact on education can be directly reflected on graduates' preparedness. Aim: The aim of this study is to study self-perceived preparedness of dental school graduates and the impact of COVID-19 on their preparedness. Materials and Methods: An online survey was designed and sent electronically to 5th year students who were graduating in 2020, dentists who graduated in 2019 and were doing their prelicensure training, and dentists who graduated before 2019. The survey was self-designed and validated by an experienced professor in the school then tested by couple of participants. The survey composed of multiple sections. Four-point Likert scale was used to assess participants' perception in all the survey sections. Results and Discussion: A total of 209 participants responded to the online questionnaire. The mean total preparedness score (TPS) for the 209 participants was 97.6 (standard deviation ± 9.7) with a range of 69-120. The mean TPS of the different classes of participants was 99.5 for the class graduated before 2019, 98.1 for the 2020 class, and 95.1 for the 2019 class. Participants felt they are confident and extremely confident doing most of the required competencies. Weakness was mainly reported in surgical extraction for 2020 graduates due to the 8 weeks loss of their training. COVID-19 had considerable impact on 59.7% of the participants and marginal to no impact on 40.3%. The highest prevalence of those who thought it had some to severe impact on their confidence was those who graduated in year 2019 (73.4%). Conclusions: The graduates who participated in the survey felt confident in performing the majority of general dentistry procedures. COVID-19 pandemic negatively impacted the confidence of all the classes of participants even those graduated before 2019.